PENGARUH MODEL PEMBELAJARAN MAKE A MATCH BERBASIS MEDIA DIORAMA TERHADAP HASIL BELAJAR IPA SD NEGERI 01 PEMULUTAN - Eli Astriana; Lukmam Hakim; Rury Rizhardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The formulation of the problem in this study is whether there is an influence of the Make a Match learning model based on diorama media on science learning outcomes at SD Negeri 01 Pemulutan. The purpose of this study was to determine the increase in learning outcomes when using the Make a Match learning model based on diorama media on natural science material at SD Negeri 01 Pemulutan. The research method used in this research is Quantitative Experimental with the Quasi-Experimental Design type and the experimental research design used in this research is the Nonequivalent Control Group Design. The population in this study were all fourth-grade students at SD Negeri 01 Pemulutan. The sample in this study used Cluster Random Sampling and the sample in this study was class IV B as the experimental class and class IV C as the control class. Based on the results of research data analysis on calculations using the t-test, it was found that the t-count was 4,469 > t-table 2,021 with a Sig value. (2-tailed) <.001 <0.05 so that Ho is rejected and Ha is accepted. So it can be concluded that the Make a Match learning model based on diorama media has an effect on the results of learning science in class IV SD Negeri 01 Pemulutan.